Peran Permainan Target dalam Meningkatkan Ketepatan Teknik Shooting Menggunakan Kaki Bagian Dalam Pada Atlet Futsal - Pardiman Pardiman; Raden Akhmad Atqoo (Journal on Education, 2025)
The target game is a game where the player will get a score if the ball or other similar projectiles are thrown or hit in a directed manner on a predetermined target and the fewer hits to the target the better, target game training is related to a specific target or object. knowing the study of the target game training literature on the accuracy of shooting using the inner foot in the game of futsal. The research method used is a literature study consisting of several sources such as primary sources and secondary sources. With the results of research from various sources, it can be concluded that the target game training method on shooting accuracy using the inner leg of the futsal game is as follows: "There is an effect of target game training before and after the shooting using the inner leg of the futsal game by using the target game training method. . So it can be concluded that the target game training method has a significant effect on the accuracy of shooting using the inner foot in the game of futsal